Measurement of isolated photons accompanied by jets in deep inelastic ep scattering - Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Aggarwal, R; Antonelli, S; Antonioli, P; Antonov, A; Arneodo, M; Arslan, O; Aushev, V; Aushev, Y; et al. (2012)
The production of isolated high-energy photons accompanied by jets has been measured in deep inelastic ep scattering with the ZEUS detector at HERA, using an integrated luminosity of 326pb -1. Measurements were made for exchanged photon virtualities, Q 2, in the range 10 to 350GeV 2. The photons were measured in the transverse-energy and pseudorapidity ranges 4